(untitled) - Blij, H.J. de (Hoboken, NJ, 2005)
An unsurpassed art and illustration program, with map projections from Goode's World Atlas Building upon the strength and success of deBlij & Muller's best-selling Geography: Realms, Regions, and Concepts,_this book_offers all of the content that has made Regions the definitive World Regional Geography text but in a briefer, technological-rich package. At about one-half the length of most world regional texts, the text offers brief regional descriptions, applications of core concepts, and definitions to acquaint the reader with the spatial interconnections between the human and physical systems of the earth._
Keywords: Geography; Textbooks